Effect of sediment supply on geometry of wave ripples: preliminary results of flume experiment - Sekiguchi, Tomohiro; Yamaguchi, Naofumi; Taki, Toshifumi (Journal of the Sedimentological Society of Japan, 2022)
In order to examine the effects of sediment supply on wave-ripple morphology, we conducted flume experiments under similar hydraulic conditions with three different sediment supply rates. In a case with relatively low sediment supply rate, the wave-ripple morphology was maintained. As the sediment supply rates increased, the initial wave ripples flattened over a larger area. Under the hydraulic conditions and sediment grain size in the present experiments (water depth: 0.3 m, wave period: 1.0 s, wave height: 76-78 mm and sediment grain size: 0.20 mm), flattening of wave ripples was observed at bed aggradation rate of 32 mm/min. This result suggests that the previous formation models of wave-ripple lamination, in which wave ripples are unaffected by sediment supply, do not necessarily hold when the sediment supply rate is high.